2013
DOI: 10.1016/j.jrp.2013.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Constructs of social and emotional effectiveness: Different labels, same content?

Abstract: a b s t r a c tSocial skills, interpersonal competence, political skill, emotional intelligence, empathy, and emotion recognition ability all belong to the domain of social and emotional effectiveness constructs (SEECs). To date, it remains unclear to what extent SEECs overlap and differ and how they fit in the nomological net of personality. We examined the overall dimensional structure of 32 scales from five self-report and three performance-based instruments, representing the above-mentioned constructs. Fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 20 publications
(32 reference statements)
0
24
0
1
Order By: Relevance
“…Given the criticisms surrounding trait EI (e.g., Antonakis, 2004;Conte, 2005;Harms & Credé, 2010;Schulte et al, 2004;Schlegel et al, 2013;Van Rooy et al, 2005), it was imperative to enrich the literature of the field by systematically investigating the extent to which the construct has incremental predictive utility. Although small, the overall effect-size confirms the distinctiveness and theoretical importance of trait EI.…”
Section: Discussionmentioning
confidence: 99%
“…Given the criticisms surrounding trait EI (e.g., Antonakis, 2004;Conte, 2005;Harms & Credé, 2010;Schulte et al, 2004;Schlegel et al, 2013;Van Rooy et al, 2005), it was imperative to enrich the literature of the field by systematically investigating the extent to which the construct has incremental predictive utility. Although small, the overall effect-size confirms the distinctiveness and theoretical importance of trait EI.…”
Section: Discussionmentioning
confidence: 99%
“…In Buhrmester et al's (1988) developmental work, the ICQ demonstrated adequate test-retest stability, with Pearson correlation r's ranging from .69 to .89. None of the non-U.S. studies conducted with the ICQ (i.e., Górska, 2011;Kanning, 2006, Schlegel et al, 2013, however, had yet replicated this finding, in that none addressed test-retest reliability. Our Study 2, thus, is the first to confirm the fair to excellent temporal stability of the ICQ also from a non-U.S. context.…”
Section: Versions Of the Interpersonalmentioning
confidence: 97%
“…For example, a German (Kanning, 2006), a Polish (Górska, 2011), and a French (Schlegel, Grandjean, & Scherer, 2013) versions were recently introduced and examined. In Buhrmester et al's (1988) original studies, the internal consistency of the ICQ scales ranged from .77 to .87 (Cronbach's alpha), and a series of factor analyses confirmed the hypothesized, five-factor structure of the ICQ.…”
Section: Introductionmentioning
confidence: 99%
“…However, a smaller number of studies have employed network analysis to study psychopathology at the construct level (i.e., where nodes represent conceptually related symptom/behavior aggregates; Costantini et al, 2015; Costantini & Perugini, 2012; Hoorelbeke, Marchetti, De Schryver, & Koster, 2016; Schlegel, Grandjean, & Scherer, 2013). The construct level and symptom level approaches taken by these investigators demonstrate the flexibility of the network approach in characterizing psychopathology phenomena at various levels of analysis.…”
Section: Using Network Analysis To Visualize Elements Of the Vicious mentioning
confidence: 99%